Pengaruh Current Ratio, Total Assets Turnover, Dan Net Profit Margin Terhadap Penurunan Laba Perusahaan Industri Pertambangan Nikel Periode 2021-2024 - Nugraha, Muhammad Apriyandi Dian; Hakim, Heikal Muhammad Zakaria (Peneliti.net, 2025)
This study aims to identify the factors influencing the decline in profits of companies focused on the nickel mining sector, based on the argument that Indonesia's nickel mining has great potential to become one of the largest nickel producers in the world. However, in 2024, three nickel mining companies experienced profit declines of more than 50%. The financial ratios used to assess the companies' profit conditions in this research are current ratio, total asset turnover, and net profit margin. The software employed to test and analyze the hypotheses is SPSS version 24. The study results indicate that current ratio and total asset turnover have a significant negative effect on the decline in company profits, while net profit margin has a significant positive effect on the decline in profits.